Monocytoid B cell lymphoma: clinical and prognostic features of 21 patients. - Cogliatti, S B (1990)
Twenty one patients between 34 and 83 years of age with monocytoid B cell lymphoma (MBCL) of the lymph node were studied. The histological picture characteristically showed broad strands of medium sized cells with irregularly shaped nuclei and a fairly broad rim of slightly basophilic cytoplasm. One case developed into a centroblastic polymorphic lymphoma. Bone marrow infiltration was documented in three cases and leukaemic conversion in one case of MBCL. Seven patients had enlarged spleens. Eight patients were in stage I, five in stage II/IIE, two in stage IIIs and six in stage IV at the time of diagnosis. Of 18 patients subsequently followed up, eight were in complete remission, two in partial remission, and three were undergoing treatment at completion of the study; five patients had died. Relapse occurred in nine patients and was a common feature of MBCL. The prognosis of MBCL was comparable with that of other low grade malignant lymphomas. Fourteen patients presented with primary nodal lymphoma. In seven patients with nodal MBCL, however, a concomitant low grade B cell lymphoma of the mucosa-associated lymphoid tissue (MALT) was also found in the stomach (n = 4), nasopharynx (n = 1), salivary glands (n = 1) and thyroid gland (n = 1). Two of these cases developed into high grade lymphoma. These extra-nodal manifestations were found simultaneously with MBCL in five patients. In another two patients, however, these symptoms occurred in a later phase of the disease. It is emphasised that adequate staging procedures must be carried out in any case of nodal MBCL to exclude underlying low grade B cell lymphoma of the MALT.